Transitional solutions for the displaced in the Horn of Africa - Majidi, N; Dadu-Brown, S (Refugee Studies Centre, University of Oxford, 2016)
Refugees can contribute significantly to the economy of countries of refuge. Legal, structural and political backing is crucial to strengthen this contribution and maximise the opportunities that are present.